A 28-Year History of HIV-1 Drug Resistance and Transmission in Washington, DC - Gibson, Keylie M.; Steiner, Margaret C.; Kassaye, Seble; Maldarelli, Frank; Grossman, Zehava; Pérez-Losada, Marcos; Crandall, Keith A. (Frontiers in Microbiology, 2019)
Washington, DC consistently has one of the highest annual rates of new HIV-1 diagnosis in the United States over the last ten years. To guide intervention and prevention strategies to combat DC HIV infection, it is helpful to understand HIV transmission dynamics in a historical context. Towards that aim we have conducted a retrospective study (years 1987 to 2015) of 3,349 HIV pol sequences (1,026 bp) from 1,996 individuals living in the DC area belonging to three different cohorts. We coupled HIV sequence data with clinical information (sex, risk factor, race/ethnicity, viral load, subtype, anti-retroviral regimen) to identify circulating drug resistant mutations (DRM) and transmission clusters. Using phylogenetic methods and the Stanford HIV database, we found 13 subtypes and circulating recombinants. We also detected 41 transmission clusters in the DC area of which 78.0% involved men who have sex with men (MSM) and 31.7% involved heterosexuals. Given the maturity of the DC HIV epidemic and high HIV mutation rate, these newly identified transmission clusters may have formed in previously unknown high-risk areas within the city. DRMs caused changes in 24 and 61 amino acids in protease and reverse transcriptase, respectively. NRTI, NNRTI, and RT SDRMs contained the highest total number of DRMs (1,104-1,600) with 64-97 unique DRMs present and the highest proportion (>20%) of resistant individuals. Individuals who acquired infection through blood transfusion or perinatally had the highest DRM prevalence (sequences with one or more DRMs/total sequences) at 58.33%. Heterosexuals (43.94%), MSM (40.13%), and unknown (44.26%) risk factors showed similar prevalence of DRMs, while injection drug users had a lower prevalence (33.33%). Finally, there was a 60% spike in the number of codons with DRMs between 2007 and 2010. Current and past patterns of HIV transmission and DRM dynamics described here will help to direct public health actions to high-risk areas and infected individuals, so more efficient measures to inform, diagnose and treat HIV infection in Washington, DC can be developed.